2017
DOI: 10.3892/or.2017.5919
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated exosomic miR-23b-3p plays regulatory roles in the progression of pancreatic cancer

Abstract: Pancreatic cancer (PC) is one of the most lethal malignances. Identification of biomarkers for early diagnosis of PC is a key imperative. MicroRNAs (miRNAs) have been shown to be valuable biomarkers in the context of several cancers. Exosomes refer to vesicles released by the tumor cells at the early stage of disease. Thus, detection of miRNA in exosomes can be used as a potential biomarker for PC. In this study, we profiled serum levels of miRNAs in patients with chronic pancreatitis (CP) and PC; the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“… Proliferation [ 108 ] miR-221-3p Inhibitor miR-23b-3p PANC-1 cells PANC-1 cells CA-19-9 miR-23b-3p expression in sera or that in the exosomes isolated from sera showed a close relationship with CA-19-9 expression. Proliferation and metastasis [ 103 , 109 ] miR-141, miR-375 PCa cells Serum / miR-141 and miR-375 were associated with recurrent (metastatic) PCa following radical prostatectomy metastasis [ 110 ] miR-1290, miR-375 PCa cells Plasma / Various RNA species and changes in exosomal RNA contents are robust candidates as clinical biomarkers for advanced PCa Survival prognosis [ 111 ] miR-19b PCa cells Urine / Active secretion of miR-19b containing vesicles by tumor cells Diagnosis [ 112 ] Isomirs of miR-21, miR-375 and miR-204 PCa cells Urine MARCKS, BTG2, PTEN, RECK The miRNA-read-length of miR-204, miR-21 and miR-375 showed clear differences when comparing controls with PCa patient samples. Progression [ 113 , 114 ] miR-141 PCa cells Serum / Exosomal miR-141 is upregulated in the serum from patients with PCa compared with patients with benign prostate hyperplasia or the healthy volunteers Metastasis [ 115 ] miR-200c-3p Urine PCa cells ZEB1, ZEB2, SNAIL2 miRNA re-expression inhibits prostasphere formation, decreases clonogenic survival, and reduces NOTCH1 and LIN28B gene expression, the drivers of self-renewal.…”
Section: Introductionmentioning
confidence: 99%
“… Proliferation [ 108 ] miR-221-3p Inhibitor miR-23b-3p PANC-1 cells PANC-1 cells CA-19-9 miR-23b-3p expression in sera or that in the exosomes isolated from sera showed a close relationship with CA-19-9 expression. Proliferation and metastasis [ 103 , 109 ] miR-141, miR-375 PCa cells Serum / miR-141 and miR-375 were associated with recurrent (metastatic) PCa following radical prostatectomy metastasis [ 110 ] miR-1290, miR-375 PCa cells Plasma / Various RNA species and changes in exosomal RNA contents are robust candidates as clinical biomarkers for advanced PCa Survival prognosis [ 111 ] miR-19b PCa cells Urine / Active secretion of miR-19b containing vesicles by tumor cells Diagnosis [ 112 ] Isomirs of miR-21, miR-375 and miR-204 PCa cells Urine MARCKS, BTG2, PTEN, RECK The miRNA-read-length of miR-204, miR-21 and miR-375 showed clear differences when comparing controls with PCa patient samples. Progression [ 113 , 114 ] miR-141 PCa cells Serum / Exosomal miR-141 is upregulated in the serum from patients with PCa compared with patients with benign prostate hyperplasia or the healthy volunteers Metastasis [ 115 ] miR-200c-3p Urine PCa cells ZEB1, ZEB2, SNAIL2 miRNA re-expression inhibits prostasphere formation, decreases clonogenic survival, and reduces NOTCH1 and LIN28B gene expression, the drivers of self-renewal.…”
Section: Introductionmentioning
confidence: 99%
“…P<0.05 was considered to indicate a statistically significance. (20), including non-small cell lung cancer and gastric cancer, by acting on different signaling pathways. the present study aimed to increase our understanding of the association between mir-23b-3p level and ia.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggested that high levels of miRNA-23b-3p are detected in exosomes from PANC-1 cells. In this study, it was investigated that exosome-mediated transfer of miRNA-23b-3p can promote the proliferation, migration and invasion of PANC-1 cells [11] (Figure 1 and Table 1).…”
Section: Effects Of Evs and Their Cargo Molecules On Pancreatic Cancermentioning
confidence: 99%